Coronary ostial compromise in aortic valve replacement: An avoidable complication. (June 2015) - Farid, Shakil; Page, Aravinda; Howell, Neil; Goddard, Martin; Abu-Omar, Yasir; Jenkins, David P; Nashef, Samer AM
Background: We sought to determine the incidence of hospital death due to surgical compromise of the coronary ostia in aortic valve replacement. The mechanism of coronary ostium blockage was also investigated. Methods: A retrospective review was conducted of prospectively collected clinical data and autopsy findings in 322 patients who died in hospital after aortic valve replacement with or without concomitant procedures in a single institution from January 1998 to March 2013. Results: Over the 15-year period, more than 17 surgeons performed 7507 aortic valve replacements with or without other procedures. The mean age of the patients was 70.8 ± 11.78 years and 63% were male. Bioprosthetic valves were used in 75%, mechanical valves in 24.7%, and homografts in only 0.3%. Early mortality for all patients (combined, emergency, and redo procedures) was 4.29% (mean logistic EuroSCORE 10.7). There were 322 deaths after procedures involving the aortic valve. Autopsy examinations were carried out in all patients and showed that 3.4% ( n  = 11) of deaths were at least partly attributed to encroachment on one or both coronary ostia. Causes of ostial compromise included the valve sutures, the valve sewing ring, and the aortotomy suture line. Conclusions: Coronary ostial compromise in aortic valve replacement is a very rare but real problem occurring in at least 0.15% of aortic valve replacements and contributing to or directly causing one in every 29 aortic valve replacement deaths. Surgeons should have a high level of awareness of the risk of this rare but fatal and avoidable complication.